DIRECT EFFECT OF COMORBID MENTAL DISORDERS ON THE CLINICAL COURSE OF ALCOHOLISM - Axmadjonovich, Gaybiyev Akmal; Mirxamzayevna, Mamurova Mavludaxon; Temirpulotovich, Turayev Bobir (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study focuses on the growing concern of mental disorders combined with alcohol addiction, highlighting the need for medical examination by both narcology and psychiatry specialists. The objective is to explore the challenges related to the prevention, treatment, and rehabilitation of this comorbid condition. Methods: A comprehensive review of existing research and clinical practices was conducted, with an emphasis on the collaboration between narcologists and psychiatrists in managing patients with this dual diagnosis. Various case studies and treatment protocols were analyzed to understand the multidisciplinary approach required for effective care. Results: The study reveals significant complexities in treating individuals with both mental disorders and alcohol addiction. The findings suggest that integrated care from both narcology and psychiatry specialists leads to better patient outcomes. However, challenges remain in providing effective prevention and rehabilitation strategies due to the multifaceted nature of the disorder. Novelty: This research introduces a novel perspective on the importance of a dual-specialist approach to managing comorbid mental health and alcohol addiction issues. It emphasizes the need for a more unified and collaborative treatment framework that can address the intertwined nature of these conditions.